Use of lateral calcaneal flap for coverage of posterior heel defects (Mediscope, 2017)
Lateral calcaneal flap is frequently used for coverage of lateral calcaneum and posterior heel defects. We conducted a prospective study using lateral calcaneal artery flap to cover posterior heel defects from July 2011 to June 2015 in the Department of Burn and Plastic Surgery, Khulna Medical College to observe the clinical outcome of use of lateral calcaneal artery flap. A total number of ten soft tissue defects in posterior heel with and without exposed Achilles tendon or calcaneus due to different causes were reconstructed with lateral calcaneal artery flap. All ten flaps survived completely with no subsequent breakdown of the skin, even after regular wearing of normal shoes. The flap donor sites were grafted with split-thickness skin grafts in all cases. Partial graft loss was noted in two cases which were eventually healed spontaneously with dressing without the need for a secondary graft. Epidermal necrosis developed in one case which was ultimately healed with conservative treatment. There was no loss of sensation in flap area but sensory disturbance at the lateral part of the dorsum of foot was found in all cases. Our results were satisfactory in terms of coverage adequacy, perioperative morbidity, and functional and aesthetical outcomes. The lateral calcaneal artery skin flap can be used safely to provide sensory skin coverage in posterior heel defects.Mediscope Vol. 4, No. 1: Jan 2017, Page 5-10